Implementing Quizizz Paper Mode for Digital Learning in Marginal Education Settings: A Case Study in Malaysia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Indonesian diaspora students in overseas non-formal centers face pedagogical disengagement due to high activity, short attention spans, and limited digital infrastructure. Baseline observations revealing 4–5 minute attention fragments highlight a critical gap: current educational digitalization assumes stable internet and 1:1 device ratios, neglecting low-resource contexts. This program implements and evaluates Quizizz Paper Mode as an adaptive, low-infrastructure digitalization strategy. Employing a participatory qualitative-descriptive design, the intervention integrates structured gamified quizzes via physical barcode cards across three systematic phases. Observational metrics demonstrate significant shifts: participation exceeds 96%, sustained attention extends to ~12.8 minutes, and automated scoring reduces grading time by >70% with 98% accuracy. These findings prove that meaningful digitalization relies on pedagogically structured interaction design, not hardware proliferation. The program contributes a replicable evidence-based framework for inclusive assessment, offering broad implications for transforming marginalized community learning into interactive, sustainable academic spaces.